Crime victims: the new «icon» of Bulgarian penal policy? - Chankova, D. (KSU Publ., 2013)
This article explores the latest development of crime victims related policies and practices in Bulgaria. The newest achievements are identified and analyzed. The relevant operative legislation is scrutinized. Both the strong and the weak points of its implementation are commented. The application of restorative justice, as an essential element of the modern penal policy orientated towards crime victims, is promoted. The challenges, related to the transposition of the new European Directives, concerning victims, are discussed.
Қылмыс құрбандары: Болгария қылмыстық саясатының жаңа «белгісі» ме?
Жертвы преступлений: новый «icon» Болгарии уголовная политика?
Keywords: crime victims; protection of victim’s rights; compensation; restorative justice; Bulgaria and EU